2015
DOI: 10.1097/ijg.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study Comparing Ex-PRESS to Trabeculectomy

Abstract: There was no statistically significant difference between the trabeculectomy and Ex-PRESS groups regarding IOP, success rates, complications, additional interventions, and bleb morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 19 publications
5
77
2
Order By: Relevance
“…Dahan et al 8 randomised fellow eyes of 15 patients and after a mean follow-up of 23.6 months reported better success rates with the Ex-PRESS implant, although there was no difference in mean intraocular pressure (IOP). The other two studies found no difference in success rates between Ex-PRESS and trabeculectomy, with follow-up periods of 1 and 2 years, respectively 2 6…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Dahan et al 8 randomised fellow eyes of 15 patients and after a mean follow-up of 23.6 months reported better success rates with the Ex-PRESS implant, although there was no difference in mean intraocular pressure (IOP). The other two studies found no difference in success rates between Ex-PRESS and trabeculectomy, with follow-up periods of 1 and 2 years, respectively 2 6…”
Section: Introductionmentioning
confidence: 89%
“…Three-year follow-up data of subjects enrolled in our 1-year prospective RCT comparing Ex-PRESS with trabeculectomy were obtained 2. Charts were reviewed retrospectively for missed data if the study visit had passed and prospectively to obtain 2-year and 3-year results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EXP was developed in an effort to make filtration surgery more straightforward. Nonetheless, it seems that the efficacy and safety profile of the EXP are not superior to standard trabeculectomy [44][45][46][47]. Only a few studies directly comparing AGV and EXP have been published.…”
Section: Ahmed Glaucoma Valve Versus Ex-press Shuntsmentioning
confidence: 99%